A community of communities? similarity and difference in Welsh rural community studies - Day, Graham (Economic & Social Studies, 1998)
Work in the community studies tradition has been accused of perpetuating a static, over-integrated conception of community. Recent critics of communitarian thought similarly attack the idea of community for its exclusiveness, and for privileging unity over difference. A review of the classic Welsh rural community studies shows that although much in them supports these claims, they also allow an alternative conception of communities as loosely structured networks lending themselves to subtle distinctions and flexible boundaries. This less repressive version of community is endorsed by recent accounts of the social construction of community in the context of changing rural social relations.
Keywords: Community studies; Wales; Social relations; Rural communities